2019
DOI: 10.1186/s12903-019-0800-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of early childhood caries in Cambodia

Abstract: Background The Southeast Asian Forum for Early Childhood Caries identified the need for more epidemiological surveys involving preschool children. To date, the only data on Early Childhood Caries in Cambodia come from convenience samples and only using the basic dmft index without measurement of the early signs of disease. Methods A cross-sectional survey on an epidemiological sample of Cambodian preschool children was conducted in conjunction with the fourth follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 8 publications
5
27
1
Order By: Relevance
“…These findings are consistent with earlier research, which demonstrated an association between childhood caries and negative family impacts [20][21][22][23][24][25][26]. However, all earlier research used the DMFT index, which also captures mild (usually asymptomatic) disease stages.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with earlier research, which demonstrated an association between childhood caries and negative family impacts [20][21][22][23][24][25][26]. However, all earlier research used the DMFT index, which also captures mild (usually asymptomatic) disease stages.…”
Section: Discussionsupporting
confidence: 90%
“…Childhood dental caries, when left untreated, is usually associated with dental pain and inability to eat or sleep [14][15][16][17], which in turn can negatively impact the child's daily activities, including school attendance [18,19]. Several studies have shown that untreated caries among children can have a negative impact on their families as parents feel upset and guilty, take time off work to take care of the child, and endure financial difficulties [20][21][22][23][24][25][26]. However, most of these studies did not account for important confounders during analysis, such as the family structure [20][21][22][23][24][25][26] and socioeconomic circumstances [23][24][25][26], which are known determinants of both childhood dental caries and family life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age has been evidenced to be an independent risk factor of ECC by many studies [13,20,25], and this finding was corroborated in current study. Most researches, however, evaluate 3-5-year-old children as whole with few studies access the risk factors for each age.…”
Section: Logistic Regression Analysessupporting
confidence: 90%
“…[17]. Compared to some other developing countries in Asia, Thailand (age 5: 78.5%) [18], Indonesia (age 0-5: 70.0%) [19], Myanmar (age 5-6: 81.3%) and Cambodia (age 3: 84.9%) [20], all have higher rates of ECC. While in developed countries like Japan and Singapore, the ECC rates are down to 44.4% and 49% respectively [21,22], which is significantly lower than the results of 63% obtained by statistics worldwide [23] and has already achieved the goal of less than 50% prevalence of ECC for the year of 2020 raised by WHO [24].…”
Section: Logistic Regression Analysesmentioning
confidence: 99%